EFEKTIVITAS PENGGUNAAN MEDIA WHATSAPP VIDEO CALL DALAM MENINGKATKAN HASIL BELAJAR SISWA MI KOTA MADIUN - Qurrota A'Yun, Neny (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
This study aims to find out and analyze the effectiveness of learning by using whatsapp video calls in improving the learning outcomes of MI students in the city of Madiun. This research is a descriptive qualitative research. This research includes field research with the type of case study research. Data collection was obtained from observation, interviews and document studies. The research was conducted at MI Madiun city. Based on the results of the study, it was shown that student learning outcomes at MI Madiun city could be increased through the use of whatsapp video call media. The difficulties students experience when understanding the material presented by the teacher in class can be overcome by using online media in the form of WhatsApp video calls when done at home.